An electrochemical aptasensor based on functionalized graphene oxide assisted electrocatalytic signal amplification of methylene blue for aflatoxin B1 detection. (1st August 2017) - Goud, K. Yugender; Hayat, Akhtar; Catanante, Gaëlle; M., Satyanarayana; Gobi, K. Vengatajalabathy; Marty, Jean Louis
Graphical abstract: Highlights: A new electrochemical aptasensor was developed for aflatoxin B1 using methylene blue (MB) tagged anti-aflatoxin B1 (AFB1) aptamer as signaling molecule and graphene as the signal-enhancing platform. The developed aptasensor exhibits good sensitivity, stability reproducibility and the limit of detection was in practically relevant range. Practical applications were demonstrated by analyzing beer and wine samples Abstract: In this work, we developed an electrochemical aptasensor by using methylene blue (MB) redox probe labeled aptamer as a signaling fragment and functional graphene oxide (FGO) as the signal-enlarging platform. The role of functionalized graphene oxide was not mere to serve as a covalent immobilization support for aptamer sequences, but its catalytic signal amplification behavior towards methylene blue was demonstrated for the first time in the present work. The functionalized graphene oxide was cast on screen-printed carbon electrodes (SPCE), and then the MB-tagged aptamer was covalently immobilized on SPCE by using hexamethylenediamine (HMDA) as a spacer via carbodiimide amide-bonding chemistry. Aflatoxin B1 (AFB1) analyte molecule detection was accomplished by the aptamer conjugated redox probe, which undergoes/involves a conformational change in the complex structure of aptamer consequent to AFB1 binding. The proposed assay permitted to detect AFB1 in the linear range of 0.05–6.0 ng mL −1 with a very low limit of detection (LOD) (0.05 ng mL −1 ). The present principle aptasensor was tested to screen the alcoholic beverage samples for AFB1 detection and good recovery values were obtained.